Title VII & LGBTQ Employment Discrimination: An Argument for a Modern Updated Approach to Title VII Claims - Timothy Parrington (Washington University Journal of Law & Policy, 2019)
This note addresses the now-existing circuit split in the federal courts regarding antidiscrimination protections for LGBTQ individuals under Title VII of the Civil Rights Act of 1964. The note begins by examining the history of Title VII and its interpretation in early cases following its enactment. After examining less-successful attempts at securing increased protections for LGBTQ employees, the note argues that the approach that would best serve their interests would be for courts to take a more pragmatic approach to interpreting this legislation.
Keywords: Title VII; LGBTQ; employment discrimination; circuit split; antidiscrimination; Civil Rights Act of 1964